There must be a way out: The consensual qualitative analysis of best coping practices during the COVID-19 pandemic - Halamová, Júlia; Greškovičová, Katarína; Baránková, Martina; Strnádelová, Bronislava; Krizova, Katarina (Frontiers in Psychology, 2022)
Despite the continuous efforts to understand coping processes, very little is known about the utilization of best coping strategies during the COVID-19 pandemic. In this study, we aimed to analyse the coping strategies of individuals who scored high on an adaptive coping questionnaire in order to understand the most adaptive coping strategies during the COVID-19 pandemic. We used consensual qualitative analysis (Hill et al., 1997) in a team of four researchers and one auditor. The convenience sample from which we identified the high scorers comprised 1683 participants (67% women, 32.35% men, and 0.65% did not report their gender) with a mean age of 31.02 years (SD =11.99) ranging between 18 and 77 years old. Based on their scoring in the COPE Inventory (Carver et al. 1989), nine participants were selected from the sample with the highest scores in coping skills in at least two out of its fifteen subscales. In-depth repeated interviews with six participants for the main analysis were conducted, and three were added to check the data saturation. The results showed that the most adaptive coping strategies used during the COVID-19 pandemic could be categorized into four main domains: self-compassion, compassion to others, compassion from others, and mutual compassion. The most frequently mentioned and the most elaborated upon by our respondents was the domain of self-compassion. The most interesting finding was the emergence of the fourth type of compassion, labelled mutual compassion, which referred to deliberate attempts to take care of oneself and others while suffering together in order to elevate the suffering for both. This kind of compassion might arise in the situations of collective suffering, such as a catastrophe or a pandemic and might have the additional benefit of bringing people closer to each other in difficult times.